Structure for fast photonic medium on application of SDM communication using SiO2 doped with GeO2, and F Materials. Issue 3 (17th March 2021) - Behera, Bhagyalaxmi; Varshney, Shailendra K.; Mohanty, Mihir N.
Abstract: This work presents a new approach for the design of an FMF with a Gaussian core and a trench in the cladding. For the proposed few‐mode fibre (FMF), Fused Silica (SiO2 ) is considered as a host‐material, whereas Germanium Oxide(GeO2 ) and Fluorine(F)are taken as the dopant for large data transmission. The mole percentages of the dopant material along with the fibre profile parameters are varied to achieve 10 linearly polarized (LP) modes through the proposed FMF. The proposed FMF structure is tested and verified through simulated experiments. The results indicate the proposed FMF structure with the mole percentage 11.5% of GeO2, 2% of F, and the normalized full‐width‐half‐maximum (FWHM) of the core in the range of 4 to 10 supports 10 LP modes in the order of LP01, LP11, LP21, LP02, LP31, LP12, LP41, LP22, LP03, and LP51 . The effective index difference ( Δn eff ) between the adjacent LP modes is maintained greater than 1 × 10 − 3 and a weakly coupled 10x10 Gbps SDM transmission link is established through intensity‐modulation and direct‐detection (IM/DD) using the proposed Gaussian core‐FMF. The link performance is analysed, verified and an acceptable bit‐error‐rate (BER) of 10 −20 is achieved over 50 km without amplifiers.